Shear bond and rebond strengths of four composite systems (Mustansiria Dental Journal, 2024)
which are chemically—cured composite such as Two—past and No—mix systems in whiclthe composite set by chemical reaction; Light—cured composite system, in whicl:composite set by light exposure; and Dual—cured composite system, by which thcomposite cured by chemical reaction and light exposure. Thus it is necessary tt.investigate and compare the commonly used composite bonding systemsThis study was aimed to determine and compare the shear bond and reboncstrength of: Two—past composite system (Concise, 3M, Unitek USA), No—mix composite,system (Right—On, TP Orthodontics UK), Light—cured composite system (Transbond XT.)M Unitek USA), and Dual—cured composite system (Sono—Cem ESPE, Germany3,Fifty six upper premolars were divided into four groups of fourteen, each groupmesh—backed metal advant edge brackets were bonded to the buccal surface ofthe teethusing one of the composite system according to the instruction of manufacturer. Then.bonded samples were thermocycled in an attempt to simulate oral circumstancesThe samples were subjected to shear force using the universal compressionmachine apparatus, then the results were recorded in Megapascal (Mpa). The remainingcomposite on the buccal surface of the tooth was removed by hand sealer and polished, anew bracket was bonded to the buccal surface of the tooth using the same type ofcomposite system. The rebonded samples were tested under shear strength using the.universal compression machine apparatus and the results were again recorded in Mpa,The data were statistically analyzed using descriptive analysis, ANOVA test.Dtu1can’s Multiple Range Test and Student’s t—test at p g 0.0lThe results showed that the Concise had no significant higher bond shear strengththan the Transbond and Sono—Cem composite systems, and there was signilicant increasebond strength of the Concise than the Right—On composite systems. Furthermore, therewere no significant differences in bond shear strength among the Right—On, Transbond.and Sono—Cem composite systems